STRATEGI PENGEMBANGAN AGROINDUSTRI BERBASIS BIJI KAKAO DI DESA POYUYANAN KECAMATAN PASSI BARAT KABUPATEN BOLAANG MONGONDOW - Ni Kadek Puspitasari; Oktavianus Porajouw; Esry O.H. Laoh; Melissa L.G. Tarore (COCOS, 2015)
ABSTRACT  The purpose of this research is to identify the strenght, weakness, opportunity and threat factor in chocolate processing industrial in cacao seeds basis development agro-industry and how the development agroindustri strategy of cacao seeds in research area. Data collecti for four months starting from november until march 2015. The data used is primary and secondary data, primary data were obtained through abservation and through direct interview with respondents, namely, cacao farmers, cacao seeds collector, manager and workers and industrial agency. And secondary data were obtained through literature study such as books, journals, internet and relevant agencies. The data analysis with SWOT analysis.  From the research result was obtained: (1) result of internal enviroment analysis shows that there are five strenght factors namely, the availability of lots of cheap local labor, good skils in labors, tools and strategic location and using a high tecnology. Internal enviroment also has five weakness factor namely, there’s a lot of untrained labors, total production depends on demand, does not have certrificated for the products and not yet marketed, lack of capital and lack of industrial partnership with other agencies. The result of external enviroment analysis shows that there’s five factors can become an opportunity namely, there is no similiar efforts around the site/location, Bolaang Mongondow is a cacao producers as the main ingredient, there’s a support from the goverment, numbers of population keep increasing and a shopping lifestyle, availability of electricity, good infrastructure and communication. External enviroment also have four threat factors. Namely, increase prices of main ingredient, minimal help and support given, rivality with other products with the same main ingredient and threat of a new comer. (2) strategy of development cacao basis agroindustry is agressive strategy. Namely, keeping up the strenght to overcome the weakness inside it and also has opportunity and strenght to develop, like producing continously, taking advantage of technology to increase additional prices to cacao seeds, taking advantage from the regency government, facilities and infrastructure to promote various products, inventing a new variation, doing partnership with financial institution to increase funds and assets, gain a halal label, increase partnership in work, improve products quality and additional variations in order to facing competition, optimising the productions and to fasten the streamline of the products facility to overcome the impact of raising funds for productions and also to obtain a product certrificated and agressively doing promotions in order to reach easiness of marketing and inviting investors.     Keywords : Strategy, Agroindustry